2020
DOI: 10.14744/eej.2020.51523
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rotary and reciprocating instrumentation motions on postoperative pain incidence in non-surgical endodontic treatments: A systematic review and meta-analysis

Abstract: Objective: A systematic review and meta-analysis were conducted to determine whether there are postoperative pain differences resulting from rotary and reciprocation engine-driven instrumentation motions in non-surgical endodontic treatment or retreatment at 12, 24, and 48 hours. Methods: Four electronic databases (PubMed, Embase, Cochrane Library, and Scopus) were searched to identify randomised controlled trials that compared the effects of rotary and reciprocating in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
1
7
1
1
Order By: Relevance
“…Considering children's discomfort and the variables related to the postoperative pain, we also observed a similarity between the techniques, differently from previous studies that observed least postoperative pain for rotary techniques (16,17). Other discrepancy is related to the quality of the obturation, that was superior for mechanized methods (3).…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Considering children's discomfort and the variables related to the postoperative pain, we also observed a similarity between the techniques, differently from previous studies that observed least postoperative pain for rotary techniques (16,17). Other discrepancy is related to the quality of the obturation, that was superior for mechanized methods (3).…”
Section: Discussioncontrasting
confidence: 69%
“…Therefore, in the final regression model, we opted to keep the variable dental arch, because its association with the instrumentation time is more plausible. Actually, a higher proportion of caries occurrence in lower primary molars for younger children was observed (16,17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Repeated-measures ANOVA test determined that mean VAS scores differed significantly across five timepoints among the three methods. Another systematic review and meta-analysis conducted by Nobar et al in 2021 did not find a difference in 12, 24, or 48 h post-operative pain when reciprocating or rotary instrumentation was used for non-surgical root canal treatment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This has been made possible by the introduction of improved NiTi metallurgy and innovative instrument design, thereby simplifying the shaping procedures and consequently resulting in reduction of number of instruments and instrumentation time. Literature has reported numerous studies comparing single and multiple files, rotary and reciprocating systems ( 11 , 12 ).…”
Section: Introductionmentioning
confidence: 99%